Siderophores; iron scavengers: the novel & promising targets for pathogen specific antifungal therapy. (1st December 2016) - Balhara, Meenakshi; Chaudhary, Renu; Ruhil, Sonam; Singh, Bharat; Dahiya, Nisha; Parmar, Virinder S.; Jaiwal, Pawan. K.; Chhillar, Anil K.
ABSTRACT: Introduction: The recent emergence of resistance, toxicity paradigm and limited efficacy of conventional antifungal drugs necessitate the identification of de novo targets in fungal metabolism. One of the most critical physiological processes during in vivo pathogenesis is maintenance of iron homeostasis. The most life threatening opportunistic human fungal pathogens like Aspergillus, Candida and Cryptococcus exploit the siderophore mediated iron uptake mechanism either for survival, virulence, propagation or resistance to oxidative stress envisaged in vivo during infection. Areas covered: In this review, we will highlight the metabolic pathways; specifically siderophore biosynthesis, uptake and utilisation, triggered in the fungal pathogens in iron starving conditions and the various putative targets viable in these pathways to be recruited as novel therapeutic antidotes either via biosynthetic enzymes catalytic site inhibitors or as drug conjugates through trojan horse approach and further role in the development of fungal specific reliable diagnostic markers. Expert opinion: Siderophores are the weapons released by a pathogen to conquer the battle for iron acquisition. Hence, the fungal siderophore biosynthetic pathways along with their uptake and utilisation mechanisms represent an ideal target for pathogen specific, host friendly therapeutic strategy which would block the proliferation of parasite without causing any harm to the mammalian host.